Satisfaction and Concerns with Telemedicine Endocrine Care of Patients with Cystic Fibrosis - Rahat Ahmed; Margaret Greenfield; Christopher P. Morley; Marisa Desimone (Telemedicine Reports, 2022)
Introduction: Patients with chronic health conditions are at high risk for severe COVID-19 infections, making telemedicine for patients with cystic fibrosis (CF) and cystic fibrosis-related diabetes (CFRD) particularly relevant. There are limited data regarding provider perspectives on caring for patients with CF using telemedicine, particularly for those with CFRD. Methods: Surveys were administered to patients with CF (with and without CFRD) and to adult and pediatric endocrinologists who specialize in CF. Data were collected using Research Electronic Data Capture; t-tests were used to compare total mean scores of Likert scale questions. The differences in responses were performed using one-way analysis of variance followed by Tukey's Honest Significant Difference test. Variables were assessed for normality and we performed the Mann?Whitney test. No change in the results of the hypothesis test was found. All results were analyzed using SPSS version 27. Results: Eighteen patients (n?=?9 CFRD) and 21 providers responded. Both groups reported high satisfaction with telemedicine overall (83.3%; 71.4%), convenience (94.4%; 85.7%), and adequate time during the visit (94.4%; 76.2%), and the majority would recommend telemedicine to others (94.4%; 95.2%). Lack of in-person examination components was of more concern to providers than patients: height/weight (p?<?0.001), vitals (p?<?0.001), and glycated hemoglobin (p?<?0.001). There was no difference in provider perception in treatment of CFRD compared to type 1 diabetes (T1D). Common themes of open-ended questions included ease in attending telemedicine appointments (patients) and decrease in ?no shows? (providers). Discussion: Patient and provider satisfaction with telemedicine was high. The lack of typical components of face-to-face visits was more concerning for providers when compared to patients. Provider concern regarding lack of components specific to diabetes was similar regarding CFRD and T1D.